THE STUDY OF AGRICULTURAL MARKETING IN ART PERFORMANCE IN THE CASE OF “FESTIVAL PASAR KUMANDANG” - Cahyani Tunggal Sari (UNEJ e-Proceeding, 2012)
The aim of this research is revealing and describing agricultural marketing aspect in the art performance especially in promoting the traditional market in Indonesia. That is why this research takes Festival PasarKumandang in Solo as a unique case because it was the art performance held in the traditional market and become yearly program of Solo city. The method used in this research was qualitative research with multidiscipline approach that focuses on the agricultural marketing in art performance. The research also uses relevant theories such as agricultural marketing, marketing mix, and tourist art theory. Revealing the performing art and agricultural aspect was done by interviewing, observing, and reading literatures of performing art study and agricultural marketing while the marketing aspect was done by SWOT analysis. The results of the research showed that the art performance held in the traditional market attract societies to come. Buyers are more convenient to shop in the traditional market while the sellers feel entertained. Unfortunately, only a little amount of traditional market in Indonesia touched by creative marketing such as art performance as well as its physical view. Marketing strategy for agricultural products especially in traditional market are indispensable in order to maintain its presence in the growth of modern market.